THE INFLUENCE OF GALBLADDER ACUPRESSURE POINT 21 (JIAN JING) AND STOMACH 18 (RU GEN) IN INCREASEING BREASTMILK PRODUCTION - Amini, Rizkie Aulia; Rahayu, Sri (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The breast milk is the best food for the babies containing white blood cells, proteins and immune substances which are suitable for them. Various treatments have been applied to increase breast milk, including pharmacological and nonpharmacological methods. Among the nonpharmacological methods are complementary acupressure treatments which include gallbladder 21 (Jian Jing) and stomach 18 (Ru Gen).This study aims to determine the effect of acupressure points gallbladder 21 (Jian Jing) and stomach 18 (Ru Gen) on breast milk production in postpartum period. Methodology: This study used quasi experimental design with pretest posttest with control group design. The population of this study all postpartum mothers around the researcher?s work area in Ngesrep and Pegandan Health Center, Semarang City in May-June 2017 who met the inclusion criteria. The number of samples are 22 postpartum mothers who are in 3-7 postpartum days. The sampling technique is purposive sampling. Results: The results showed that the difference of average baby weight as an indicator of breast milk production before and after intervention was 2889 grams to 2776 grams with a difference of 112 grams in the treatment group and 2901 grams to 2683 grams with a difference of 246 grams in the control group. The statistical independence tests showed that there was an effect of acupressure point gallbladder 21 (Jian Jing) and stomach 18 (Ru Gen) on breast milk production in postpartum period (p<0.001). Conclusion: From the results study, it is expected that acupressure can be socialized and applied among health workers as one of the techniques to facilitate breast milk production in postpartum period.